IMPLEMENTASI NAFKAH IDDAH PADA PENGADILAN AGAMA WATAMPONE - Nur Tasdiq (AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2020)
Abstract: This research is about the application of iddah income for wives at the Religious Court in Watampone. The main issues regarding the legal status of iddah livelihoods, and how to determine the amount of iddah livelihoods, as well as the efforts of judges in resolving husband's cases refuse to provide iddah livelihoods. This research is a qualitative research with a normative juridical approach and a philosophical approach. The provision of livelihood in the Qur'an and the Compilation of Islamic Law in Indonesia is obligatory to be given to the wife after divorce, requested or not requested in court, as long as the divorce is not due to the wife's nusyuz. But this is not the case with his practice at the Religious Courts in Watampone. Determination of iddah income at the Religious Court in Watampone still prioritizes the agreement between the husband and wife, if an agreement is not found between them, the Panel of Judges will determine the amount by considering the husband's ability and wife's needs. Regarding the case of the husband refusing to provide iddah, the Panel of Judges took several efforts, but the efforts taken did not have a strong legal basis, even some of the efforts taken were not in accordance with the existing procedural law.AbstrakPenelitian ini mengenai penerapan nafkah iddah pada Pengadilan Agama Watampone. Pokok permasalahan tentang status hukum nafkah iddah, dan bagaimana cara penentuan jumlah nafkah iddah, serta upaya hakim dalam menyelesaikan perkara suami menolak memberi nafkah iddah. Penelitian ini adalah penelitian kualitatif dengan pendekatan yuridis normatif dan pendekatan filosofis.Ketentuan nafkah iddah di dalam  al-Qur’an dan Kompilasi Hukum Islam di Indonesia adalah wajib diberikan kepada isteri yang ditalak raj’i, diminta ataupun tidak diminta dalam persidangan, selama perceraian bukan karena nusyuznya isteri. Namun tidak demikian dengan peraktiknya di Pengadilan Agama Watampone. Penentuan nafkah iddah pada Pengadilan Agama Watampone tetap mengedepankan kesepakatan antara pihak suami dan isteri, apabila tidak didapati kesepakatan antara keduanya, maka Majelis Hakim yang akan menentukan jumlahnya dengan mempertimbangkan kemampuan suami dan kebutuhan isteri. Terkait perkara suami menolak memberi nafkah iddah, Majelis Hakim menempuh beberapa upaya, namun upaya yang ditempuh tidak memiliki dasar hukum yang kuat, bahkan beberapa upaya yang ditempuh tidak sesuai dengan hukum acara yang ada.Keywords: Implementation; Iddah; Living Rights; Religious courts.